Kojic acid-derived tyrosinase inhibitors: synthesis and bioactivity - Seyedeh Mahdieh Hashemi; Saeed Emami (Mazandaran University of Medical Sciences, 2015)
Tyrosinase is a key enzyme for melanin biosynthesis, catalyzing the oxidation of L-tyrosine to L-dopaquinone. The tyrosinase inhibition is an effective approach to control hyperpigmentation in human skin and enzymatic browning in fruits and vegetables. Kojic acid is a naturally-occurring tyrosinase inhibitor which has been clinically used to treat the hyperpigmentation of skin. However, kojic acid as a hydrophilic small-molecule has insufficient inhibitory activity and stability, with considerable toxicity. To overcome these drawbacks, synthetic derivatives of kojic acid were developed, which exhibited enhanced tyrosinase inhibitory activity and more favorable stability relative to kojic acid. In this context, the synthesis and biological activity of kojic acid derivatives as tyrosinase inhibitors have been highlighted.